2003
DOI: 10.1159/000074261
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Measurements in Fetoplacental Vessels after Maternal Betamethasone Administration

Abstract: Objective: To observe the influence of maternal betamethasone administration for fetal lung maturation on the arterial, venous and intracardiac blood flow of the fetus and the uterine arteries. Methods: Twenty-seven women with singleton pregnancies were examined before the first, and 30 min and 8, 24, 48 and 72 h after the second of two single doses of 8 mg of betamethasone. We recorded blood flow velocity waveforms of the umbilical artery (UA), the middle cerebral artery, the uterine arteries, the ductus veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
(31 reference statements)
4
19
1
3
Order By: Relevance
“…Although glucocorticoids play a role in the regulation of ductus tissue, recent studies have suggested that betamethasone, in and of itself, does not lead to clinically significant intrauterine ductus constriction. 3,4 There are only infrequent cases of idiopathic closure of the ductus arteriosus in the literature, and none of the cases we found during our literature search excluded all secondary causes, such as teas and herbal remedies. 5,6 We excluded all known secondary causes Vol.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although glucocorticoids play a role in the regulation of ductus tissue, recent studies have suggested that betamethasone, in and of itself, does not lead to clinically significant intrauterine ductus constriction. 3,4 There are only infrequent cases of idiopathic closure of the ductus arteriosus in the literature, and none of the cases we found during our literature search excluded all secondary causes, such as teas and herbal remedies. 5,6 We excluded all known secondary causes Vol.…”
Section: Discussionmentioning
confidence: 91%
“…Ductus arteriosus constriction due to NSAIDs is dependent on the dosage and duration of exposure and usually resolves 24 hours after the medication is discontinued. Although glucocorticoids play a role in the regulation of ductus tissue, recent studies have suggested that betamethasone, in and of itself, does not lead to clinically significant intrauterine ductus constriction 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…It had mild effect on the fetal heart rate (24). Although in some investigations, it was found that it did not affect Doppler parameters of UA, UtA, and MCA, in some, a decrease in Doppler indices of UA and MCA (25,26) and ductus venosus, particularly PI of MCA, was seen (27). Therefore, it is thought that variations in fetal and fetomaternal circulation in the late period (24-48 hours) of nifedipine and ritodrine in different studies are caused by a combined effect of tocolysis and betamethasone.…”
Section: Discussionmentioning
confidence: 96%
“…So it could be said that Betamethasone causes short-term changes in fetal blood flow. However, this effect seems to be mild and reversible and does not appear to contraindicate the use of corticosteroids to promote fetal lung maturation [115]. Therefore, it could be mentioned that long term dexamethasone usage my result with decreased maternal blood velocity which would negatively affect angiogenesis mechanisms as maternal blood itself contains angiogenesis related proteins.…”
Section: The Effects Of Glucocorticoids On Fetal and Placental Angiogmentioning
confidence: 99%